2018
DOI: 10.1007/s00408-018-0139-1
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Bronchoalveolar Lavage and Transbronchial Biopsy in Patients with Hypersensitivity Pneumonitis

Abstract: Our study suggests that the combination of TBBX with BAL significantly increases the likelihood that the procedure will provide adequate additional information to allow a confident MDD diagnosis of HP and may reduce the need for SLB in the diagnostic workup of HP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
41
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 36 publications
3
41
1
1
Order By: Relevance
“…BAL as the diagnostic test is poorly characterized in patients with fibrotic cHP and a wide range conditions can be associated with lymphocytosis [29][30][31]. Adams et al also demonstrated the combination of transbronchial biopsy and BAL increases the likelihood that the procedure will give adequate information to allow a confident diagnosis of cHP as well as possibly reducing the need for more invasive surgical lung biopsy [31]. However, this study also showed that the diagnostic yield of BAL was low [31].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…BAL as the diagnostic test is poorly characterized in patients with fibrotic cHP and a wide range conditions can be associated with lymphocytosis [29][30][31]. Adams et al also demonstrated the combination of transbronchial biopsy and BAL increases the likelihood that the procedure will give adequate information to allow a confident diagnosis of cHP as well as possibly reducing the need for more invasive surgical lung biopsy [31]. However, this study also showed that the diagnostic yield of BAL was low [31].…”
Section: Discussionmentioning
confidence: 63%
“…In the Delphi survey, bronchoscopy with bronchoalveolar lavage (BAL) and transbronchial biopsy was recommended to increase diagnostic confidence [16]. BAL as the diagnostic test is poorly characterized in patients with fibrotic cHP and a wide range conditions can be associated with lymphocytosis [29][30][31]. Adams et al also demonstrated the combination of transbronchial biopsy and BAL increases the likelihood that the procedure will give adequate information to allow a confident diagnosis of cHP as well as possibly reducing the need for more invasive surgical lung biopsy [31].…”
Section: Discussionmentioning
confidence: 99%
“…BAL as the diagnostic test is poorly characterized in patients with fibrotic cHP and a wide range conditions can be associated with lymphocytosis [26][27][28]. Adams et al also demonstrated the combination of transbronchial biopsy and BAL increases the likelihood that the procedure will give adequate information to allow a confident diagnosis of cHP as well as possibly reducing the need for more invasive surgical lung biopsy [28]. However, this study also showed that the diagnostic yield of BAL was low [28].…”
Section: Discussionmentioning
confidence: 63%
“…Adams et al also demonstrated the combination of transbronchial biopsy and BAL increases the likelihood that the procedure will give adequate information to allow a confident diagnosis of cHP as well as possibly reducing the need for more invasive surgical lung biopsy [28]. However, this study also showed that the diagnostic yield of BAL was low [28]. Therefore, while not diagnostic on its own, BAL can helpful in the diagnosis of HP when combined with other clinical findings.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation